Perspectivismo con objetividad, causal y temporal - Liz Gutiérrez, Antonio Manuel; Vázquez Campos, Margarita (Daimon Revista Internacional de Filosofia, 2018)
It has been suggested that the only plausible way to integrate causality in the scientific image of the world is through a subjectivist causal perspectivism. Causation would exist only from the point of view of an agent capable of doing things. The conception of time associated with such causal perspectivism is certain temporal perspectivism that is also subjectivist. Following some ideas of Ramsey, Huw Price is a recent exponent of these approaches, which are rooted in Russell’s critique of the notion of causality and in McTaggart’s irrealism about time. We analyze this line of thought and argue for an objectivist interpretation of those perspectivisms. It will be crucial a distinction between perspectives and the subjects capable of adopting them, as well as an analysis of the conditions for adopting perspectives.